Gambaran Bayi Berat Lahir Rendah Dengan Asfiksia di RSUP Haji Adam Malik - Insana Kamilia Tampubolon (Majalah Kedokteran Andalas, 2021)
Objective: to observe the description of the condition of asphyxia in infants with low birth weight (LBW) at Haji Adam Malik General Hospital Medan. Methods: The research design is descriptive research. Data collection and collection used secondary data from medical records at the Haji Adam Malik General Hospital Medan in the period January 2016 to May 2019. The research sample was taken using a total sampling technique. Results: 33 infants with low birth weight with asphyxia were included in this study. The incidence of infants with low birth weight with asphyxia has decreased every year with the highest incidence in 2016 which was 2.98% of the total live births. The majority of babies are female (54.54%), including low birth weight (84.84%). The majority of pregnant women aged 20-35 years (87.87%) with spontaneous delivery (78.78%) and the most gestation period was below 37 weeks (84.84%). Most cases of asphyxia in infants with LBW are born to primiparous mothers. Conclusion: The picture of babies with LBW with asphyxia is generally the same as the picture in previous studies.